Early Clinical Exposure in U.S. Dental Schools and Correlation with Earlier Competencies Evaluation. Issue 2 (11th February 2020) - Yu, Amy; Pagni, Sarah E.; Park, Sang E.; Karimbux, Nadeem
Abstract: Early clinical exposure (ECE), defined as any interaction with patients prior to the portion of the curriculum when den‐ tal students spend most of their time at school as a primary provider, is a growing trend in curriculum reform across U.S. dental schools in the 21 st century. The aims of this study were to characterize the types of ECE implementation in U.S. dental schools and determine if ECE correlated with earlier clinical competency assessments. In September 2018, the academic deans of all 66 U.S. dental schools were invited to respond to an eight‐item electronic survey about ECE at their schools. Representatives of 40 schools submitted complete responses, for a response rate of 60.6%. Among the respondents, 85% reported their schools started their principal clinical experience (PCE), the portion of the curriculum when students spend most of their time as the primary provider for patients, during the last quarter of Year 2 or the first quarter of Year 3. Respondents at all 40 schools reported offering some form of ECE as part of the formal curriculum, with shadowing and performing dental prophylaxis the most commonly of‐ fered types. No statistically significant associations were found between specific types of ECE and related Commission on Dental Accreditation (CODA) clinical standards for both formative and summative assessments. Although U.S. dental schools have been incorporating more ECE into their curricula over the past decade, these findings suggest that it has not led to earlier clinical competency assessments.